Radiochemical Methodologies Applied to Analytical Characterization of Low and Intermediate Level Wastes from Nuclear Power Plants (Brazilian Journal of Radiation Sciences (BJRS), 2019)
The aim of this work is to present radiochemical methodologies developed at CDTN/CNEN in order to answer a program for isotopic inventory of radioactive wastes from Brazilian Nuclear Power Plants.  In this program  some radionuclides, 3H, 14C, 55Fe, 59Ni, 63Ni, 90Sr, 93Zr, 94Nb, 99Tc, 129I, 235U, 238U, 238Pu, 239+240Pu, 241Pu, 242Pu, 241Am, 242Cm e 243+244Cm, were determined  in Low Level Wastes (LLW) and Intermediate Level Wastes (ILW) and a protocol of analytical methodologies based on radiochemical separation steps and spectrometric and nuclear techniques was stablished.